HUBUNGAN POLA ASUH DEMOKRATIS TERHADAP KEMAMPUAN BERBAHASA ANAK KELOMPOK B DI TK âAISYIYAH GONILAN KARTASURA KABUPATEN SUKOHARJO - Fitria Anggraini Syuharyoso, Nurul (Muhammadiyah University Press, 2015)
This study aims to determine of democratic parenting relationship between language skills in children TKAisyiyah Gonilan Kartasura Sukoharjo in the academic year 2014/2015. This research is quantitative descriptive. Population of this research areÂ children in kindergarden Aisyiyah Gonilan Kartasura with a total of 100 children. The samples of population are in this study 30 students group B TK Aisyiyah Gonilan. The sampling used in this study is clusterrandom sampling. Methods of data collection is a questionnaire sheet premises. The data are takenÂ the primary data for parenting pattern byÂ parents and secondary data for childern language ability. The analysis technique used is a product moment correlation technique. Results of the data analysis isÂ rhitung 0682 rtabel0,349Â Â with significant value 0,000 whereas this value is smaller than the significance level of 0.01. Based on the results ofÂ dataÂ study concluded that democratic parenting can improve language skills of kindergarden B TK Aisyiyah Gonilan Kartasura Sukoharjo academic year 2014/2015.